Myanmar Country Environmental Analysis : Environmental Impact Assessment System Diagnostic - World Bank (World Bank, Washington, DC, 2019)
Myanmar has relied heavily on natural resource exploitation to sustain economic growth, and serious environmental issues are emerging, underlining the importance of transparent and robust Environmental Impact Assessment (EIA) system. There are growing concerns around the impacts of the large-scale development, including deforestation, depletion of inland and coastal fisheries, land degradation, flooding and landslides, biodiversity loss, and the deterioration of water and air quality. A functioning EIA system is critical in identifying and managing the potential impacts of large-scale development and striking the balance between economic development, environmental conservation, and social inclusion.